2018
DOI: 10.1002/mame.201800496
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Routes to Functionalized Graphene Nanofillers Tuned for Lightweight Carbon/Hydrocarbon Composites

Abstract: Graphite exfoliation by shear‐induced dry and wet processes and especially mechanochemistry represent attractive routes to carbon nanofillers. Dry ball‐milling of graphite in a planetary mill under gas pressure is a scalable and environmentally benign one‐step process, which requires neither hazardous solvents nor tedious separate functionalization and purification steps. Gas type, pressure, and milling duration govern average particle size, shape, and functionalization. Ball‐milling under Ar yields hydroxylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 181 publications
(291 reference statements)
0
3
0
Order By: Relevance
“…However, the versatility of environmental control during the process and additional energy supply for the chemical reaction from the ball's kinetic energy makes the ball-mill method a more versatile tool for functionalization. 456,457 As shown in Fig. 12(a), performing the ball-mill process under the desired gas or liquid environment functionalizes 2D materials with selected groups.…”
Section: Functionalization Techniquesmentioning
confidence: 99%
“…However, the versatility of environmental control during the process and additional energy supply for the chemical reaction from the ball's kinetic energy makes the ball-mill method a more versatile tool for functionalization. 456,457 As shown in Fig. 12(a), performing the ball-mill process under the desired gas or liquid environment functionalizes 2D materials with selected groups.…”
Section: Functionalization Techniquesmentioning
confidence: 99%
“…Several studies have shown that the formation of graphene sheets can be aided by mechanochemical methods, where graphite is ball milled under specific conditions and graphene in excellent quality can be obtained. [131][132][133] Such a methodology may be equally applicable to zeolites, potentially…”
Section: Perspective and Outlookmentioning
confidence: 99%
“…In general, the advantages of mechanochemical approaches are no requirement of a solvent for carrying out the reaction (solvent-free conditions), faster reaction, and considerably pure products. Due to these reasons, ball milling has been successfully used in polymerization reactions, , multicomponent organic syntheses, , including gaseous reagents and carbon materials, crystal preparation, , asymmetric organic syntheses, and some other miscellaneous applications in medicinal and pharmaceutical chemistries. , …”
Section: Introductionmentioning
confidence: 99%